Motif Tapis Lampung Dalam Street art Kontemporer: Kajian Gaya dan Persepsi Publik - Arsy Khairunnisa; Oca Yuliza Razak; Rahmat Prayogi; Mulyanto Widodo (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This study examines the adaptation of Lampung Tapis motifs in contemporary Street art as a form of visual dialogue between traditional aesthetics and modern Urban culture. The urgency of this research arises from the declining awareness of local cultural symbols among younger generations and the dominance of global visual trends that tend to overshadow regional artistic identity. The main objective of this study is to analyze how Street artists reinterpret Lampung Tapis motifs to construct new meanings of Cultural representation while maintaining authenticity and contextual relevance in the modern era. Employing a Qualitative descriptive method, this research collected data through direct field observations, visual documentation, and semi-structured interviews with Street artists and members of the art community in Bandar Lampung. The data were analyzed using Visual semiotics and Cultural representation theory to interpret the Symbolic meanings of color, composition, and form found in the artworks. The findings reveal that Lampung Tapis motifs in Street art function not merely as decorative elements but as cultural signifiers that embody identity, resilience, and the continuity of local traditions. The study concludes that integrating Lampung Tapis motifs into Urban visual art represents a strategic approach to cultural preservation, strengthening Local identity and fostering appreciation for traditional values within the dynamics of Global visual culture.